The Role of Cardiovascular Magnetic Resonance in Sports Cardiology; Current Utility and Future Perspectives - Androulakis, Emmanuel (Curr Treat Options Cardiovasc Med, 2018)
PURPOSE OF REVIEW: Cardiovascular magnetic resonance (CMR) is frequently used in the investigation of suspected cardiac disease in athletes. In this review, we discuss how CMR can be used in athletes with suspected cardiomyopathy with particular reference to volumetric analysis and tissue characterization. We also discuss the finding of non-ischaemic fibrosis in athletes describing its prevalence, distribution and clinical importance. RECENT FINDINGS: The strengths of CMR include high spatial resolution, unrestricted imaging planes and lack of ionizing radiation. Regular physical exercise leads to cardiac remodeling that in certain situations can be clinically challenging to differentiate from various cardiomyopathies. Thorough morphological assessment by CMR is fundamental to ensuring accurate diagnosis. Developments in tissue characterization by late gadolinium enhancement and T1 mapping have the potential to be powerful additional tools in this challenging clinical situation. Using late gadolinium enhancement, it is also possible to detect non-ischaemic fibrosis in athletes who do not have overt cardiomyopathy. The mechanisms of this fibrosis are unclear; however, it does appear to be clinically important. We also review data on the prevalence of non-ischaemic fibrosis in athletes. SUMMARY: CMR is a powerful tool to aid in the diagnosis of cardiomyopathy in athletes. It may also have a future role in assessing fibrosis related to long-term participation in sport.